Analisis Konten Media Sosial Yang Efektif Untuk Menarik Minat Generasi Z Dalam Memilih Perguruan Tinggi: (Studi Kasus Politeknik Pariwisata Prima Internasional) - Khalim, Abdul; Fitriyana, Dian (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to evaluate the effectiveness of social media content strategies implemented by Politeknik Pariwisata Prima Internasional in attracting the interest of Generation Z as prospective students. Through a sequential exploratory approach, this study combines qualitative methods, in the form of in-depth analysis of social media content, and quantitative, through an online survey of 50 Generation Z respondents who are active on the institution's social media platforms. The analysis results show that content related to campus life, student activities, and overseas fieldwork experience (Prakerin) dominates the institution's posts. These contents have proven effective in arousing curiosity and relevance among Generation Z, who often seek information about campus life before deciding to enroll. However, this study also identified several areas that need improvement. Although the visual quality of the content is quite good, it still needs to be optimized. Filters, visual effects, and more attractive graphic designs can increase the appeal of the content. In addition, the level of content interactivity is still relatively low. Features such as quizzes, polls, and Q&A sessions with students can increase engagement and provide opportunities for prospective students to interact directly with the institution. The survey results confirm the findings of the qualitative analysis. Respondents stated that content that shows real-life students and internship experiences is very interesting. Generation Z tends to be attracted to content that is authentic and relevant to their experiences. In addition, they also appreciate content that is entertaining, informative, and up-to-date